Dampak Pengaruh Teknologi Terhadap (Cyber Crime) Tindak Pidana Serta Analisis Hukum Terkait - Faturohman Faturohman; Rachmat Putra Hidjriana; Rizky Zendra Rahayu (QAIMUDDIN: Journal of Constitutional Law Review, 2022)
Technology that fundamentally changes the way we interact and transact, also has a significant impact on cyber crime. In preparing the journal, we carried out an in-depth analysis of the influence of modern technology, such as artificial intelligence, blockchain, and the Internet of Things, on the increasing incidence of cyber crime. It found that continued technological innovation creates new opportunities for cybercriminals, while unaddressed security weaknesses increase the risk of attacks. A deep understanding of these dynamics is key to developing effective and proactive solutions to combat cybersecurity challenges in today's digital era. Legal and cyber security constraints that have not been able to keep up with the pace of technological development are the main causes of the increasing number of cyber crimes. Therefore, a deep understanding of the relationship between technology and cybercrime is very important to formulate effective security strategies in this digital era